HUBUNGAN KECERDASAN EMOSIONAL DENGAN SIKAP SOSIAL SISWA KELAS XI AKUNTANSI SMK NEGERI 3 PONTIANAK - Wegi Agusti; Purwanti Purwanti; Sri Lestari (Universitas Tanjungpura, 2018)
Emotional intelligence is a person's ability to express and control emotions in the right way. A person's attitude is strongly influenced by emotions or ways of expressing emotions. Likewise the connection with social attitudes which is a manifestation of the expression of one's emotions in carrying out relationships or social interactions. Attitude is a follow-up to even the manifestation of one's emotions. This study aims to determine the relationship of Emotional Intelligence with Social Attitude Students Class XI Accounting in SMK Negeri 3 Pontianak. The method used is descriptive method and research form using relationship study. The population in this study as many as 155 students and samples 48 students class XI Accounting. This study uses a quantitative approach. Data collection techniques used indirect communication techniques and data collection tools using questionnaires. Data analysis techniques using the formula percentage and product moment correlation. Based on the results of this study stated that there is a Relationship of Emotional Intelligence With Social Attitude Students Class XI Accounting at SMK Negeri 3 Pontianak which is included in the category of